2018
DOI: 10.1103/physrevc.98.045804
|View full text |Cite
|
Sign up to set email alerts
|

Critical examination of constraints on the equation of state of dense matter obtained from GW170817

Abstract: The correlation of the tidal polarizabilities Λ1-Λ2 for GW170817 is predicted by combining densematter equations of state (EOSs) that satisfy nuclear physics constraints with the chirp mass and mass asymmetry for this event. Our models are constrained by calculations of the neutron-matter EOS using chiral effective field theory Hamiltonians with reliable error estimates up to once or twice the nuclear saturation density. In the latter case, we find that GW170817 does not improve our understanding of the EOS. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
336
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 360 publications
(362 citation statements)
references
References 47 publications
25
336
1
Order By: Relevance
“…Similarly, including better constraints on the theoretical uncertainty at low densities by matching to chiral effective field theory with theoretical uncertainties from truncating series expansions [25][26][27][28] should further constrain our priors. We note, though, that GW170817 produces posterior processes that already tend to follow the prior relatively closely below ρ nuc (see Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, including better constraints on the theoretical uncertainty at low densities by matching to chiral effective field theory with theoretical uncertainties from truncating series expansions [25][26][27][28] should further constrain our priors. We note, though, that GW170817 produces posterior processes that already tend to follow the prior relatively closely below ρ nuc (see Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The sampling of configuration space in VMC and GFMC simulations gives access to many important properties of light nuclei such as spectra, form factors, transitions, low-energy scattering, and response functions. Auxiliary Field Diffusion Monte Carlo (AFDMC) [10,98] uses Monte Carlo techniques to additionally sample the spin-isospin degrees of freedom, enabling studies of, for example, nuclei up to A = 16 [99,100] and neutron matter [90,91,101,102,103] that is so critical to determining the structure of neutron stars. QMC simulations have surely proved to be very valuable in attacking many nuclear-structure problems over the last three decades but require local chiral interactions as input.…”
Section: Chiral Effective Field Theorymentioning
confidence: 99%
“…These calculations have been successfully used to study the EOS of neutron stars, and it has been found that the resulting equations of state are consistent with astrophysical observations of pulsar masses. The EOS have also been used to study gravitational waves from neutron-star mergers [102,113,114].…”
Section: Infinite Mattermentioning
confidence: 99%
“…One possibility is a deconfinement phase transition from bound hadronic states to liberated quark states. The effect of a strong first-order phase transition on tidal deformabilities of the neutron star in the context of GW170817 event has been explored by a number of * jiajieli@itp.uni-frankfurt.de † sedrakian@fias.uni-frankfurt.de ‡ alford@physics.wustl.edu groups [5][6][7][8][9][10][11][12][13][14][15] showing that the hadron-quark phase transition at low enough density, ρ 2-3ρ 0 , where ρ 0 is the nuclear saturation density, relaxes the tension between the inferred tidal deformabilities and those predicted by purely hadronic models without a phase transition. Of particular interest in this context is the emergence of twin stars, where purely nucleonic and hybrid stars have the same masses, but different radii [6].…”
Section: Introductionmentioning
confidence: 99%